2018
DOI: 10.1128/jvi.01930-17
|View full text |Cite
|
Sign up to set email alerts
|

Minor Capsid Protein L2 Polytope Induces Broad Protection against Oncogenic and Mucosal Human Papillomaviruses

Abstract: The amino terminus of the human papillomavirus (HPV) minor capsid protein L2 contains a major cross-neutralization epitope which provides the basis for the development of a broadly protecting HPV vaccine. A wide range of protection against different HPV types would eliminate one of the major drawbacks of the commercial, L1-based prophylactic vaccines. Previously, we have reported that insertion of the L2 epitope into a scaffold composed of bacterial thioredoxin protein generates a potent antigen inducing compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…L2 is the minor capsid protein of HPV, and we have previously shown that an Nterminal region comprising amino acids 20-38 can induce broadly cross-neutralizing antibody responses when inserted into, and displayed on, the surface of P. furiosus thioredoxin (Pf Trx) (12,19,37). We have also documented a sizeable increase in immunogenicity upon fusion of Pf Trx-L2 to a selfassembling protein module (named OVX313) derived from the complement-binding protein C4bp and conversion of the antigen into a heptameric nanoparticle form (24,25,43). Therefore, we asked whether further multimerization of the basic Pf TrxL2 antigen would promote an additional increase in immunogenicity.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…L2 is the minor capsid protein of HPV, and we have previously shown that an Nterminal region comprising amino acids 20-38 can induce broadly cross-neutralizing antibody responses when inserted into, and displayed on, the surface of P. furiosus thioredoxin (Pf Trx) (12,19,37). We have also documented a sizeable increase in immunogenicity upon fusion of Pf Trx-L2 to a selfassembling protein module (named OVX313) derived from the complement-binding protein C4bp and conversion of the antigen into a heptameric nanoparticle form (24,25,43). Therefore, we asked whether further multimerization of the basic Pf TrxL2 antigen would promote an additional increase in immunogenicity.…”
Section: Resultsmentioning
confidence: 98%
“…A major step in Pf TrxL2 antigen development has been the construction of a Pf Trx-displayed polytope comprising tandemly repeated L2 epitopes from seven different mucosal oncogenic and one cutaneous HPV types. This was followed by genetic fusion of the PfTrx-L2(8x) (Pf Trx8mer) polytope with OVX313, a selfassembling polypeptide that promoted covalent heptamerization of the antigen into a super-scaffolded form, leading to a 5-to 10-fold increase in neutralizing antibody titers compared to the corresponding monomeric antigen (24,25). The resulting nanoparticle vaccine afforded protection against 26 mucosal and cutaneous HPV types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, immunizations with an L2 peptide conjugated to thioredoxin [44,45], immunizations with concatemers of L2 protein fused to a self-adjuvanting protein (flagellin) [46,47] as well as immunizations with a concatemer of L2 proteins derived from different HPV types [48,49] have been used. More recently, an L2 polypeptide and a heptamerizing coiled-coil polypeptide OVX313 fused to a nanoparticle derived from a thermostable thioredoxin has been used [50][51][52]. These approaches have enhanced the immunogenicity of L2 peptides, especially immunization with the nanoparticle thioredoxin-L2-OVX313 candidate vaccine.…”
Section: L2 Proteinmentioning
confidence: 99%
“…These approaches have enhanced the immunogenicity of L2 peptides, especially immunization with the nanoparticle thioredoxin-L2-OVX313 candidate vaccine. The nanoparticle candidate vaccine offers protection against more than 14 HPV types [50]. Although the aforementioned strategies enhanced immune responses, the responses were observed mostly when large doses (up to 25 µg) of antigens, coupled with large amount of adjuvant with multiple immunizations regimens were used.…”
Section: L2 Proteinmentioning
confidence: 99%